Estimating leaf appearance rate and phyllochron in safflower (Carthamus tinctorius L.) - Streck,Nereu Augusto (2005)
Safflower may be an interesting option for the flower market, either as fresh or dried cut flower. Estimating the leaf appearance rate and the phyllochron (the time interval between the appearance of successive leaves) is important for calculating the number of emerged leaves (NL) on the plant, which is an excellent measure of plant development. The objective of this study was to estimate the leaf appearance rate and the phyllochron in safflower (Carthamus tinctorius L.). An experiment was conducted in Santa Maria, RS, Brazil, inside an 8 x 15m plastic greenhouse. Sowing was on 03 October 2003 and emergence was on 08 October 2003. The experimental design was a randomized complete block design with three replications. The main stem NL was measured twice a week from 24 October 2003 to 15 November 2003 in four plants per replication. Daily growing degree days above a base temperature (5°C) and accumulated thermal time (TT) were calculated. The NL was linearly regressed against TT. The angular coefficient of the linear regression is the LAR (leaves/ °C day) and the phyllochron (°C days/leaf) was estimated by the inverse of the angular coefficient of the linear regression. The LAR was 0.0467 ± 0.0203 leaves/ °C day and the phyllochron was 25.5 ± 14.6°C days/leaf.